Physiological stress responses and meat quality traits of kids subjected to different pre-slaughter stressors - Zimerman, Maria (2011)
Crossbred Criollo Neuquino castrated male kids, 6 months of age and 24 kg of live weight, were used to investigate the effects of pre-slaughter stressors on physiological characteristics and meat quality attributes. On four separate days, 16 kids were randomly assigned to one of the four pre-slaughter stressor treatments (4 kids per treatment per day): (A) no stress (control); (B) 24 h of food deprivation (fasting); (C) physical stress of forced exercise by an animal handler for 30 min at approximately 3 km/h (exercise); or (D) psychological stress by placing kids in a pen with barking dogs for 5 min (fear). Fasted goats had greater (P < 0.05) hematocrit, urea and total protein concentrations than controls. Exercised kids had greater (P < 0.05) cortisol concentration than controls and goats exposed to barking dogs had greater (P < 0.05) hematocrit and cortisol concentration compared with controls. Even though the stressors imposed on the kids induced changes in blood constituents typically associated with the stress response, the intensity and/or duration of these stressors had little or no effect on meat quality.